Losing Moment Project Accessories: The Impact of Product Quality & Promotion toward Repurchase Intention through Costumer Satisfaction - Kamitha, Adella; Fachri, Helman; Ramadhan, Muhammad Ebuziyya Alif (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This research investigates the influence of Product Quality and Promotion on the Repurchase Intention of Losing Moment Project accessories in Pontianak, with Customer Satisfaction acting as a mediating variable. The study utilizes an associative approach, with a sample of 100 respondents comprising individuals who have previously purchased and used Losing Moment Project accessories. Data analysis is conducted using Structural Equation Modeling (SEM) via SmartPLS 3.0 software. The findings from hypothesis testing demonstrate that Product Quality positively and significantly impacts both Customer Satisfaction and Repurchase Intention. While Promotion positively and significantly affects Customer Satisfaction, it does not directly influence Repurchase Intention. Additionally, Customer Satisfaction has a significant positive impact on Repurchase Intention. Mediation analysis further reveals that Product Quality and Promotion, when mediated by Customer Satisfaction, exhibit a significant positive influence on Repurchase Intention.